Banking, risk and crises in Europe : from the global financial crisis to COVID-19 /: from the global financial crisis to COVID-19. (2023) - Karkowska, Renata; Korzeb, Zbigniew; Matysek-Jędrych, Anna; Niedziółka, Paweł
No abstract available